MORALE GROUP KEPEMIMPINAN PENDIDIKAN (Berlandaskan Tinjauan Agama, Filsafat, Sosiologi, dan Psikologi) - Nurshiddieq .; Aep Saepudin; Ishak Abdulhak; Achmad Mudrikah (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2021)
This study presents the topic "Morale Group (Moral Group) Based on Religion, Philosophy, Sociology and Psychology at the Daarul Ihsan Islamic Boarding School, Cimahi City". This study uses a descriptive method with a qualitative approach. Retrieval of data sources in this study using purposive sampling. While the data collection using research techniques with interviews, observation, literature study and documentation. The conclusion of this study is that the Morale Group (Moral Group) is very important and vital in the management of the Daarul Ihsan Islamic Boarding School in Cimahi City because in essence morals really determine the quality of a human's personality. Individual morals in groups who have al-karimah or ethical character are very vital in life in the Daarul Ihsan Islamic boarding school institution where the role of the Islamic boarding school leader will play an important role in creating students who are knowledgeable, faithful, devoted, have a noble personality, have character and are independent. In the boarding school, the leader of the pesantren will be used as a role model or role model for his students, for that the leadership of the pesantren must motivate his students more and set an example so that students can be more active in studying, worshiping and doing charity so that they will be more successful in the future. In the era of globalization which is full of challenges and the rapid development of the digitalization world which emphasizes the elements of information technology, it has become a demand for the moral quality of a santri in addition to having extensive knowledge or knowledge, he must also have the firmness of faith, morality and morals which are expected to be higher purely cognitive aspect.